Quantum and semiclassical calculations of electron transport through a stochastic system - Hardwick, David Peter Andrew (2007)
In this thesis, I present a semiclassical and quantum mechanical study of a biased superlattice with a tilted magnetic field applied. This system exhibits non-KAM chaotic behaviour which can be controlled by the ratio between the cyclotron and Bloch frequencies. I will use a semiclassical model to show that electron trajectories become unbounded when this ratio takes an integer value. These extended electron trajectories cause peaks in the electron drift-velocity, which lead to current enhancements calculated using a drift-diffusion model. Furthermore, I will explain this current enhancement with reference to the electric field and charge carrier density across the superlattice. These results will then be compared to experimentally measured current-voltage characteristics.